Gold Minerbio for CTA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
CTA's Director, Mr. Assoumou Mba, has been awarded CEFA's 'Gold Minerbio' which recognizes outstanding individual or institutional contributions in the field of international agricultural cooperation. The European Centre for Agricultural Training...